Text Entry Using a Dual Joystick Game Controller - Wilson, Andy; Agrawala, Maneesh (CHI '06 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2006)
We present a new bimanual text entry technique designed for today’s dual-joystick game controllers. The left and right joysticks are used to independently select characters from the corresponding (left/right) half of an on-screen selection keyboard. Our dual-stick approach is analogous to typing on a standard keyboard, where each hand (left/right) presses keys on the corresponding side of the keyboard. We conducted a user study showing that our technique supports keyboarding skills transfer and is thereby readily learnable. Our technique increases entry speed significantly compared to the status quo single stick selection keyboard technique.